Autologous Tissue Technique to Repair Unilateral Isolated Absence of a Pulmonary Artery. Issue 4 (July 2021) - von Stumm, Maria; Biermann, Daniel; Reichenspurner, Hermann; Gottschalk, Urda; Müller, Götz; Kozlik-Feldmann, Rainer; Riso, Arlindo; Sachweh, Jörg S.
Isolated unilateral absence of a pulmonary artery (UAPA) is a rare congenital anomaly in which one branch pulmonary artery has no connection to the main pulmonary trunk (most often there is ductal origin). Without treatment, it may lead to ipsilateral pulmonary hypoplasia and contralateral pulmonary artery hypertension. To avoid these complications, early surgical repair of UAPA is necessary. Surgical strategies include direct anastomosis between the "isolated" branch pulmonary artery (PA) and the main pulmonary trunk or creation of an interposition graft using prosthetic material or flap techniques. We describe a surgical technique using a totally autologous interposition tube graft.